Increasing Students’ Reading Comprehension through Herringbone Technique: A Case of Vocational High School - Bachtiar Bachtiar; Trival Setyadik; Juhana Juhana (Universitas Muhammadiyah Enrekang, 2023)
The Herringbone technique has been viewed as an effective method to help students to comprehend the text, and to gain the main idea of the text. In addition, the applying of the Herringbone technique engages students to be actively involved in a learning process. This study aims to find out of the effectiveness of using the Herringbone technique in increasing students’ reading comprehension in a vocational high school majoring in fisheries. This study employed Mixed Method Research (MMR) with three research tools (Pre-test and Post-test, questionnaire, and semi structure interview). The results showed that the Herringbone technique significantly affected the students’ reading comprehension. This research findings also pointed out that the students have a positive perception of reading comprehension while utilizing the Herringbone technique and the 5W1H method. The study recommends teachers to apply the Herringbone technique and the 5W1H method in teaching reading comprehension to help students increase their learning motivation and achievement.